PENGGUNAAN E-COMMERCE DALAM PEMBELAJARAN KEWIRAUSAHAN UNTUK MENINGKATKAN PROFESIONAL BISNIS RELIGIUS MAHASISWA FEBI IAIN SALATIGA - Fernaldi Anggadha Ratno (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2020)
This study examines the results of the use of entrepreneurial learning tools using information systems and digital marketing technology at the Faculty of Economics and Business IAIN Salatiga. The purpose of this study was to determine the use of digital marketing in entrepreneurship learning to improve the professional business of religious students of FEBI IAIN Salatiga. The analytical tool used is the coefficient of honesty analysis. Path coefficient analysis aims to see the significance of the magnitude of the path coefficient (regression weights estimate) to prove the influence that exists. In the two-tailed test, the results of significant influence if with a significance level of 0.05, the value of critical ratio> 1.96 and with a significance level of 0.01 value of critical ratio> 2.58. Correspondence of the direction of the path relationship with the direction of the relationship that has been hypothesized before is also considered, if the direction of the relationship (positive or negative) in accordance with the value of the critical ratio also meets the requirements, then it can be said that the influence of the tested variable has strong support. So that it is possible that with ecommerce it will be able to improve professional business for students.